MOG‐antibody‐associated disorder with hypothalamic lesions associated with hypersomnia and decrease of orexin in CSF: A case report - Menjo, Kanako; Ashida, Shinji; Murata, Shohei; Tanaka, Eijirou; Fujii, Chihiro; Tanaka, Masami; Tanaka, Keiko; Kanbayashi, Takashi; Mizuno, Toshiki (Clinical & experimental neuroimmunology, 2022)
Background Myelin oligodendrocyte glycoprotein antibody‐associated disease (MOGAD) is an inflammatory disorder of the central nervous system. Here, we are the first to report a MOGAD patient with hypersomnolence caused by bilateral hypothalamic lesions. Case presentation The case involved a 51‐year‐old female patient with MOGAD who showed hypersomnolence. She had been diagnosed with MOGAD at 50 years old and admitted due to the development of optic neuritis and encephalitis while under corticosteroid and immunosuppressant treatment. These were improved after the introduction of intravenous methylprednisolone and plasma exchange. The orexin level in the cerebrospinal fluid (CSF) was decreased to 142.2 pg/mL (<200 pg/mL) upon admission and improved to a normal level (298.3 pg/mL) after immunotherapy. Bilateral hypothalamic lesions and reduction of the orexin level in the CSF were considered associated with hypersomnia. Conclusion The orexin level in CSF was useful to monitor hypothalamic dysfunction in a patient with MOGAD.